The influence of strategic leadership in an organization: a case study : Ellerine Holdings Limited - Mathura, Vikash (Rhodes University, Faculty of Commerce, Investec Business School, 2010)
A review of the academic literature related to "strategic leadership" reveals that the performance of an organization will indeed be influenced by the application of this phenomenon. This thesis confines its research to a case study on Ellerine Holdings Limited, a multi-billion rand enterprise that trades in the competitive Southern African furniture retail industry. Following the 2007 acquisition of Ellerine Holdings Limited (EHL) by African Bank Investments Limited (ABIL), a new Chief Executive Officer (CEO) was appointed to develop and to lead the strategic changes that were envisioned for EHL. The research examines how the performance of EHL has been influenced since the appointment of Toni Fourie as the new CEO in February 2008. Boasting a reputation borne from his previous successes in organizational transformation, Fourie was ABIL's first-choice leader for this challenge. Fourie displays qualities, attributes, behaviours and traits that are characterized by the phenomenon of "strategic leadership" . He has been the focus of media attention for the aggressive strategic changes that he has introduced within the organization. A quantitative analysis of EHL's financial performance (between 2007 and 2009) indicated that there was a constant decline in the organization's PBT (Profit Before Taxation) during the period observed. However, the research determined that turbulent conditions in the macro-economic environment (such as the global economic recession in 2008 and 2009) complemented by mitigating micro-economic factors, would have adversely skewed the conclusions in this document if the research was limited to quantitative analysis alone. Hence, the researcher explored a qualitative research framework by collecting and assimilating data from available documentation, and from formal interviews that were conducted with research participants representing the organization's new leadership. These participants included the new CEO, Fourie, and the new Director of Strategy, Dr. Louis Carstens. Information was also obtained from informal discussions that were conducted with other senior executives, and with an ex general manager of one of EHL's business units, who was based in the Eastern Cape region at the time. An examination of all of this data concluded that although Ellerine Holdings Limited was not achieving all of its financialperformance objectives, there was general consensus that the CEO's strategic choices would yield the desired financial results from the mediumterm (namely, year-03 of his tenure) onwards. The CEO's optimism and conviction that his strategic interventions will address long-term financial sustainability is shared by both EHL's internal and external stakeholders. It emerged that EHL's stakeholders were satisfied with the accelerated progress reflected in the organization's non-financial performance indices. These indicators included the sowing of a new organizational culture; improved cost-base efficiencies; labour productivity; customer satisfaction; employee empowerment; innovation and creative thinking; collaborative and participative engagement; structural rationalization, and the introduction of new processes and procedures. The research from the EHL case study concluded that the phenomenon of strategic leadership can have a positive influence on various qualitative indicators within an organization. The research also determined that despite unforeseen conditions in both the macro and micro economic environments, an effective strategic leadership will remain committed to its vision, and resilient to its critics and competitors. This research further concludes that successful organizational transformation (within a macro enterprise) is ostensibly dependent on the interventions of a strategic leader who displays a specialist set of skills and behaviours. These strategic leaders have the ability to successfully shift the cognitive paradigms of their employees, thereby creating an enabling environment for the implementation of their strategic choices.
Keywords: Strategic planning -- South Africa -- Case studies; Leadership -- South Africa -- Case studies; Corporate culture -- South Africa -- Case studies; Organizational behavior -- South Africa -- Case studies; Organizational change -- South Africa -- Case studies; Furniture industry and trade -- South Africa -- Case studies